Efficient radio resource allocation scheme for 5G networks with device-to-device communication - Fareha Nizam; Mardeni Roslee; Zubaida Yusoff; Prince Ugochukwu Nmenme; Keshvinder Singh; Anwar Faizd Bin Osman; Ibraheem Abdullah Mohammed Shayea; Hafizal Mohamad (Institute of Advanced Engineering and Science (IAES), 2024)
Indexed by Scopus